Paleoenvironmental Changes Since the Late Pleistocene Revealed by Ostracodes Record in Changmu Co., Western Tibet - Song, Gao; Wang, Hailei (Frontiers in Earth Science, 2022)
A 4.9 m profile (BG-1) in Changmu Co, western Tibet, provides a continuous climate records from the Late Pleistocene to mid-Holocene, on the basis of ostracodes assemblages and shell trace elements. Results show six distinct climate change zones from 23.4 to 4.9 ka BP based on U-Th dating. The climate remained extremely cold until 13 ka BP because of the influence of the Last Glacial Maximum, which was indicated by the rare ostracodes occurring in this period. After that, the temperature rose gradually and the palaeolake (Changmu Co) enlarged. The ostracodes assemblage during this period had high abundance and diversity, although the dominance of cold water species and low Mg/Ca ratios indicate that the climate was still cold. More runoff water from a relatively warm climate entering into the lake, suggested by the increased U/Ca and Mn/Ca, led to a high lake level 13-10.5 ka BP; this trend was also verified by the decreasing Sr/Ca values. The climate changed from humid to drought between 10.5-7.9 ka BP, which was inferred from the decreased abundance of ostracodes; however, there was a short humid period from 9.5 to 9.2 ka BP suggested by increased U/Ca and Mn/Ca ratios. A gradual transition to a humid environment began at 7.9 ka BP and ended at 5.3 ka BP. After this period, an extremely arid climate occurred after rising temperature and increasing evaporation, indicated by sharply increased Mg/Ca and Sr/Ca ratios. Ultimately, the Changmu Co palaeolake shrank and dried up at some time after 4.9 ka BP. The changes in palaeoclimate in Changmu Co since the Late Pleistocene corresponded well to changes that occurred in the Westerlies dominated Central Asia, suggesting that the climate in this region was mainly controlled by Westerlies circulation.